Strategies For Optimizing Corporate Income Tax In Sharia Cooperatives - Lutfhi Husain; Siti Aminah; Puji Rahayu (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze corporate income tax optimization strategies in Sharia cooperatives through fiscal reconciliation, utilization of tax incentives under Article 31E, and the treatment of zakat. The research employs a qualitative case study approach using financial statement data of KSPPS An Nahl Berkah Jatim for the 2024 fiscal year, complemented by limited interviews with cooperative management. Data were analyzed using fiscal reconciliation techniques, tax calculation simulations, Effective Tax Rate (ETR) analysis, and a fiscal sensitivity model. The results indicate that the cooperative successfully optimized its tax burden, reflected in an Effective Tax Rate (ETR) of 14.81%, which is lower than the statutory tax rate of 22%. The application of Article 31E incentives and accurate fiscal adjustments contributed to this efficiency. Furthermore, simulation results show that treating zakat as a deductible expense reduces tax payable and improves tax efficiency. However, the absence of standardized zakat allocation and documentation limits the full utilization of these tax benefits. The findings imply that tax optimization in Sharia cooperatives is influenced not only by regulatory compliance but also by internal governance, particularly in managing Islamic social finance instruments such as zakat. This study contributes to the integration of tax planning and Islamic finance and provides practical implications for cooperatives and policymakers.